INTEGRATION MANAGEMENT OF MADRASAH AND PESATREN CURRICULUM AT MAS MIZANUL KUBRO BINJAI - Manshuruddin Manshuruddin; Charles Rangkuti (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe 1) madrasah-Islamic boarding school integrative curriculum planning at MAS Mizanul Kubro Binjai, 2) madrasah-Islamic boarding school integrative curriculum implementation at MAS Mizanul Kubro Binjai, and 3) the evaluation of madrasah-Islamic boarding school integrative curriculum at MAS Mizanul Kubro Binjai. This study used a descriptive qualitative method through an interpretive paradigm with the research site, namely Madrasah Aliyah Mizanul Kubro Binjai. Data collection techniques include non-participatory observation, in-depth interviews, and documentation studies. Data analysis uses data reduction techniques, data presentation, and conclusions and verification. The results of the study show that: 1) the integration planning of the madrasah and Islamic boarding schools curriculum at MAS Mizanul Kubro Binjai is carried out by integrating curriculum objectives and integrating the organization of curriculum content; 2) implementing an integrative curriculum for madrasah-Islamic boarding schools at MAS Mizanul Kubro Binjai is carried out by integrating academic and non-academic programs implementing the curriculum and integrating the supervision of curriculum implementation through collaboration between the head of the madrasah and the head of the Islamic boarding school in carrying out supervision; 3) evaluating the integrative curriculum of madrasah and Islamic boarding schools at MAS Mizanul Kubro, including the curriculum in context (social-cultural developments, science and technology, and the world of work), input (competency of teaching staff, readiness of students, learning media/means), process (identical and weekly), and product (mid-year and year-end evaluation)